Somatic Deletion in Exon 10 of Aryl Hydrocarbon Receptor Gene in Human GH-Secreting Pituitary Tumors - Re, Agnese; Ferraù, Francesco; Cafiero, Concetta; Spagnolo, Federica; Barresi, Valeria; Romeo, Daniela Petronilla; Ragonese, Marta; Grassi, Claudio; Pontecorvi, Alfredo; Farsetti, Antonella; Cannavò, Salvatore (Frontiers in Endocrinology, 2020)
Objective/Purpose: The aryl hydrocarbon receptor (AHR) pathway plays a critical role in the biology of Growth Hormone (GH)-secreting pituitary tumor (somatotropinoma). Germline rs2066853 AHR variant was found to be more frequent among acromegaly patients and associated with a more severe disease and with invasive somatropinoma, and with resistance to somatostatin analogs treatment in patients living in polluted areas. However, no somatic changes in AHR gene have been reported so far in acromegaly patients. On that basis, the aim of the study was to assess at the somatic level the AHR gene status encompassing exon 10 region, also because of the high rate of variants found in this genomic region. Methods: A cohort of 13 patients aged 20–76 years with biochemical, clinical and histological diagnosis of somatotropinoma was studied. DNA and RNA from pituitary tumor histological samples have been extracted and analyzed by PCR and direct sequencing for AHR gene variants, and compared with corresponding patients’ germline DNA as well as normal pituitary tissue as reference control. Results: A degenerated letter codes in the region corresponding to AHR exon 10 (c.1239-c.2056) was detected in somatotropinomas-derived DNA but not in that of matched germline and pituitary normal tissue. By multiple PCR and sequencing analysis, we observed amplification only before codon 1246 and after codon 1254, confirming the presence of a tumor-restricted somatic deletion in the 5’ upstream region of AHR exon 10. Analysis of PCR-amplified cDNA revealed a wildtype sequence of exon 9 and 10 in normal pituitary tissue, and a wildtype sequence of exon 9 and 10 up to codon 1246 and no sequence after the deletion region (c.1246-c.1254) in 6 out of 9 tumor samples. Patients carrying the germline rs2066853 AHR variant showed no somatic LOH at the corresponding genetic locus. Conclusion: This is the first demonstration of a recurrent somatic deletion in the exon 10 of the AHR gene in somatotropinomas. The functional impact of this genetic finding needs to be clarified.